1992
DOI: 10.1111/j.1476-5381.1992.tb14351.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute and chronic electroconvulsive shock on noradrenaline release in the rat hippocampus and frontal cortex

Abstract: Changes in the extracellular content of endogenous noradrenaline (NA) in frontal cortex and hippocampus were determined by in vivo microdialysis following acute and chronic electroconvulsive shock (ECS) in rats anaesthetized with chloral hydrate. Basal release of NA in the frontal cortex (4.9 ± 0.3 pg/sample) did not differ significantly from that in the hippocampus (4.6 ± 0.2 pg/sample). A single ECS resulted in an increase of NA release in the hippocampus (21.1 ± 1.3 pg/sample) and in the frontal cortex (11.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…These data suggest that a sustained release of noradrenaline over the course of ECS in the frontal cortex may have induced a compensatory down-regulation of the presynaptic α 2 -adrenoceptors in the frontal cortex but not in hippocampus, explaining why idazoxan did not have any effect on the α 2 -adrenoceptors in frontal cortex of the ECS treated rats (Thomas et al, 1992). Our data are consistent with the observations of Subhash et al (2003) and Thomas et al (1992), finding no significant differences in the hippocampal region of the ECS treated FSL and FRL rats compared to the sham treated rats, but demonstrating down-regulation in cortical regions in the FSL rats and in cortical and amygdaloid regions in the FRL rats. Moreover, the lack of alteration in receptor binding in the hippocampal region is in line with the unresponsiveness of hippocampal pydamidal neurons to norepinephrine found following ECS (de Montigny, 1984).…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…These data suggest that a sustained release of noradrenaline over the course of ECS in the frontal cortex may have induced a compensatory down-regulation of the presynaptic α 2 -adrenoceptors in the frontal cortex but not in hippocampus, explaining why idazoxan did not have any effect on the α 2 -adrenoceptors in frontal cortex of the ECS treated rats (Thomas et al, 1992). Our data are consistent with the observations of Subhash et al (2003) and Thomas et al (1992), finding no significant differences in the hippocampal region of the ECS treated FSL and FRL rats compared to the sham treated rats, but demonstrating down-regulation in cortical regions in the FSL rats and in cortical and amygdaloid regions in the FRL rats. Moreover, the lack of alteration in receptor binding in the hippocampal region is in line with the unresponsiveness of hippocampal pydamidal neurons to norepinephrine found following ECS (de Montigny, 1984).…”
Section: Discussionmentioning
confidence: 74%
“…However, it must be noted that post-mortem changes in binding do not always correlate with the in vivo functional response of receptors and increased sensitivity of amygdaloid neurons to monoaminergic transmitters has been found following antidepressant treatment (Wang and Aghajanian, 1980). A decreased density in α 2 -adrenoceptors was found by Subhash et al (2003) in cortical areas, but not in hippocampal areas, in the rat brain after chronic treatment with tricyclic antidepressants suggesting region-specific down-regulation and Thomas et al (1992) found a release of noradrenaline 24 h after the last chronic ECS treatment session in rat frontal cortex, but not in hippocampus, compared to sham treated controls. Furthermore, when Thomas et al (1992) challenged these rats with the α 2 -adrenoceptor antagonist idazoxan, increased release of noradrenaline was found in the sham treated rats in both brain regions, but in the chronically ECS treated rats, the release was only observed in the hippocampus.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations